REDESAIN TERMINAL BUS LAWANG KUARI SEKADAU DENGAN PENDEKATAN ARSITEKTUR HUMANIS - Awi Febril Putra Pratama; Muhammad Nurhamsyah; Irwin Irwin (JMARS: Jurnal Mosaik Arsitektur, 2022)
Sekadau is one of the regencies located in West Kalimantan. As the economy develops, transportation facilities and infrastructure in Sekadau Regency are also increasingly needed. It aims to support the smooth mobility of passengers and goods. One of the supporting elements of the transportation system is the station which functions in controlling, supervising, and regulating the passenger and goods transportation system and being one of the node points of public transportation routes. The only bus station in Sekadau Regency is Lawang Kuari Station which is a type B terminal. This station is located in Sungai Ringin Village, Sekadau Hilir District. Even though they already have a station, the enthusiasm of the Sekadau community to use public transportation services is still very low. This is due to the government's lack of attention to station empowerment, both in terms of fulfilling facilities and maintaining buildings and areas. Another problem in the Lawang Kuari Terminal area is the functional problem of this area itself. In this station redesign, the author uses a Humanist Architecture approach in order to increase comfort in the station, so that the Sekadau community pays attention to the existence of Lawang Kuari Station. The Humanist Architecture approach places more emphasis on small-scale elements that are an important part of society. This approach seeks to improve the quality of existing designs and design decisions are more focused on the needs of the community.